Crisis and Security of Criticism - Maziar Mohaymeni (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the Philippe Daros’s narration of the history of European literary criticism after the Second World War, three main periods are distinguished. First, a formalist/structuralist period, centered by language and linguistic approaches, which is a negative reaction to the horrors of War and a symbol of desire to forget the History. In the second period, the revival of historical approaches makes that the Time is situated at the center of criticism, more or less simultaneously to the emergence of a “littérature de témoignage”, which is a direct or indirect witness of the "Catastrophe". The third period – ours – begins when the literary representation of the most routine dimensions of “little lives”, here and now, pushes the criticism towards a “humanistic” reading of this kind of “crisis of historical consciousness” which characterizes the contemporary humanity.  When it seems that each of these periods in Europe has followed a lawful evolution, while European contemporary criticism tries to explain the laws of this evolution and uncover mankind's crises at various times, nowadays Iranian critique still has its own ease in linguistic and textual studies. Beyond discussions about convergence, divergence, updating, or timing of humanistic and linguistic approaches, this paper speaks of a process in which each of these approaches becomes a “safe” environment for deterrence and prevents the immediate confrontation with Human and Language. This security threatens, not only the authenticity of the criticism, but also its existence, which depends on its “critical” conditions.